(untitled) - Holzschlag, Molly E. (San Francisco, Calif., 2003)
CSS is finally supported by all modern web browsers, empowering Web designers to do what they've been hungering to do for years: control layout more precisely, use color more effectively, and expand typographic options beyond the frustrating limitations of the past. So where to begin? Where can you get design-focused instruction on CSS while learning the technical details?
Keywords: Web sites,Cascading style sheets,HTML (Document markup language); Design